2021
DOI: 10.1002/soej.12497
|View full text |Cite
|
Sign up to set email alerts
|

Externality and COVID‐19

Abstract: Negative infectious disease externalities are less prevalent in the absence of government intervention and less costly to society than is often supposed. That is so for three reasons. (1) Unlike externality‐creating behaviors in many classical externality contexts, such behaviors are often self‐limiting in the context of infectious disease. (2) In market economies, behaviors that may create infectious disease externalities typically occur at sites that are owned privately and visited voluntarily. Owners have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 32 publications
(17 reference statements)
1
35
0
Order By: Relevance
“…For example Farboodi et al (2020) and Luther (2020) found that individual responses to the virus were substantial and happened before lockdowns were mandated. Leeson and Rouanet (2021) point out the various ways this endogenous response self-limits the externality of infection, which reduces the presumed rationale for lockdowns in the first place. 10.…”
Section: Discussionmentioning
confidence: 99%
“…For example Farboodi et al (2020) and Luther (2020) found that individual responses to the virus were substantial and happened before lockdowns were mandated. Leeson and Rouanet (2021) point out the various ways this endogenous response self-limits the externality of infection, which reduces the presumed rationale for lockdowns in the first place. 10.…”
Section: Discussionmentioning
confidence: 99%
“…Hayek’s perspective, however, questions the capacity of humans to generate and to process the relevant ‘data’ in a neutral and objective manner. When little or no objective data may be available to assess the sizes or directions of externalities or whether private actions are sufficient to internalise them (on such actions, see Leeson & Rouanet, 2021 ) then Foucauldian ‘power-knowledge’ claims may assume considerable significance with ‘externalities’ used as a rhetorical device to seek power over other actors or to redistribute rights and resources through what public choice theory would describe as rent seeking actions. Grow Sun and Daniels ( 2016 ) refer here to the important role played by ‘externality entrepreneurs'.…”
Section: Public Health and The Road To Serfdom: The Problem Of Infectious Diseasesmentioning
confidence: 99%
“…In-person schooling appears to have contributed to the spread of previous seasonal flus (Cauchemez et al, 2008 ). However, prevention efforts are expected to be different during (and perhaps also following) a more dangerous pandemic such as COVID-19 (Philipson, 2000 ), especially in an organization where transmission can occur among fellow members (Leeson & Rouanet, 2021 ; Mulligan, 2021b ). We already know that in-person schools took many extra precautions during COVID-19 that often were absent in the wider community and were absent during flu seasons.…”
Section: Introductionmentioning
confidence: 99%
“… 34 Unlike, say, carbon emissions, infectious diseases are local externalities because the disease is transmitted in geographic proximity. See also Mitchell ( 1912 ), Zinberg ( 2021 ) and Leeson and Rouanet ( 2021 ). …”
mentioning
confidence: 99%